Penyusunan Indeks Beranotasi Surat Kabar Singgalang Bersubjek Pendidikan Koleksi Perpustakaan Universitas Negeri Padang - Putra, Putra; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractIn this paper discussed about the preparation of an annotated index of newspapers Singgalang Bersubjek Education library collection State University of Padang. The purpose of the writing of this paper are: 1) Described the preparation of an annotated index of newspapers Singgalang Educational Bersubjek State University Library collection; 2) Describes the constraints and the preparation of an annotated index of newspapers Singgalang bersubjek Education library collections of the University of the country. The methods used in the writing of this paper is a descriptive research method that is gathering data directly from the original sources, i.e. newspapers Singgalang library collections of the University of the country.Based on the data Analyzer, few things can be summed up as follows. The first stage in the preparation of an annotated index are: a) doing the observations on the availability of newspapers with the result there are 51 Singgalang articles bersubjek education; b selection) newspaper articles note that newspapers Singgalang contains articles bersubjek Education dikolom opinion; c) makes the newspaper's description lists the day, date, year published, page where articles found; d) create annotations after reading the entire contents of the article; e) determines the keywords that describe the subject matter of the problem of the article; f) making article index surta news which includes provisions in the writing of the author's name, article title and keywords; g) Drafting annotated index of articles on education; typing h) annotated index, title index, an index of author and keyword indices. Second, in the preparation of an annotated index of newspapers Singgalang Bersubjek Education there are obstacles faced as follows: a) constraints at the time of observation is a collection of newspapers can be overcome with a collection of newspapers should be placed and arranged on the shelves neatly collection according to the order of the month and year of publication; b) constraints at the timeof selecting appropriate collection of newspapers can be addressed by grouping newspapers berdasrkan newspapers name, month and year of publication.Keywords: index, annotations, education